Unsteady RANS and detached-eddy simulations of flow around a circular cylinder in ground effect - Nishino, T; Roberts, G; Zhang, X (2008)
Unsteady Reynolds-averaged Navier-Stokes (URANS) simulations and detached-eddy simulations (DES) were performed of flow around a circular cylinder placed near and parallel to a moving ground, on which substantially no boundary layer developed to interfere with the cylinder. The results were compared with experiments previously reported by the authors to examine how accurately the URANS and DES can predict the cessation of von Kármán-type vortex shedding and the attendant critical drag reduction of the cylinder in ground effect. The DES, which were performed in a three-dimensional domain with spanwise periodicity imposed, correctly captured the cessation of the vortex shedding, whereas both two- and three-dimensional URANS also predicted it but at a much smaller gap-to-diameter ratio compared with the experiments. The wake structures of the cylinder predicted by the DES were in good agreement with the experiments in both large- and small-gap regimes, and also in the intermediate-gap regime, where the DES captured the intermittence of the vortex shedding in the near-wake region. Based on the results obtained, further discussions are also given to the reason why the von Kármán-type vortices in the URANS solutions incorrectly 'survived' until the cylinder came much closer to the ground. © 2007 Elsevier Ltd. All rights reserved.